Heterotriangulene-based unsymmetrical squaraine dyes: synergistic effects of donor moieties and out-of-plane branched alkyl chains on dye cell performance - Karjule, Neeta; Munavvar, Fairoos M. K.; Nithyanandhan, Jayaraj (Journal of Materials Chemistry A, 2016)
Unsymmetrical squaraine sensitizers with two different donor moieties, triphenylamine (NSQR) and heterotriangulene (NSQ1–3), for dye-sensitized solar cells (DSSCs) have been designed and synthesized. These dyes utilize the indolium moiety to control charge recombination dynamics at the TiO2-dye-electrolyte interface by connecting linear and branched alkyl functionalities. In the present study, an efficient heterotriangulene (HT) donor and a branched alkyl group at sp3-C atoms were strategically incorporated to increase the power conversion efficiency (PCE) of zwitterionic dyes by improving photo-current density (Jsc) and open-circuit potential (Voc) of the cell. Among these four dyes, NSQ3 exhibited the highest efficiency of 6.73% with a Jsc of 18.74 mA cm−2, Voc of 0.53 V, and fill factor (ff) of 68.3%, without any co-adsorbent under an irradiance of 100 mW cm−2 (simulated AM 1.5G sunlight). In the presence of 3α,7α-dihydroxy-5β-cholanic acid (CDCA), NSQ1, NSQ2 and NSQ3 showed an efficiency of 7.07%, 7.38% and 7.17%, respectively. Despite the low Voc, far red light harvesting efficiency, reduced dye aggregation, long lifetime (τ) of injected electrons and high quantum efficiency of NSQ1–3 played constructive roles in achieving high PCE efficiency. Deceleration of charge recombination for NSQ dye cells was further studied by electrochemical impedance spectroscopy (EIS) and open-circuit photo-voltage decay (OCVD) measurements.

Homo- and heterodimeric dyes for dye-sensitized solar cells: panchromatic light absorption and modulated open circuit potential - Sil, Manik Chandra; Sudhakar, Vediappan; Singh, Ambarish Kumar; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ChemPlusChem, 2018)
The design of dyes for panchromatic light absorption has attracted much attention in the field of dye-sensitized solar cells (DSSCs). An approach to enhance panchromatic light absorption utilizes mixtures of complementary light-absorbing dyes as well as dyes with specific anchoring groups that facilitate interfacial charge transfer with TiO2. Dipole-dipole interactions between the dye molecules on the surface broaden the spectrum, which results in decreased DSSC device performance. However, controlled aggregation of dyes results in broadening the spectral profile along with enhanced photocurrent generation. To control the dye-dye interaction, dimeric dyes with different dipole lengths D-1-D-sq, D-sq-D(sq)were systematically designed and synthesized. The photophysical and electrochemical properties were evaluated and the E-HOMO and E-LUMO levels were determined; these energy levels determines the electron injection from E-LUMO of the dye to E-CB of TiO2 and regeneration of oxidized dye by the electrolyte, respectively. The absorption spectra of D-sq-D-sq, D-1-D-sq were broadened in solution compared to model dye D-sq; this indicates that the dye-dye interaction is prominent in solution. In D-1-D-sq excitation energy transfer between photoexcited D-1 and D-sq was explained by using Forster resonance energy transfer (FRET). The homodimeric dye showed a device performace of 2.8 % (V-oc 0.607, J(sc) 6.62 mA/cm(2), ff 69.3 %),whereas the heterodimeric dye D-1-D-sq showed a device performance of 3.9 % (V-oc 0.652 V, J(sc) 8.89 mA/cm(2), ff 68.8 %). The increased photocurrent for D-1-D(sq)is due to the panchromatic IPCE response compared to D-sq-D-sq. The increased V(oc)is due to the effective passivation of the TiO2 surface by the spirolinker, and the effective dipole moment that shifts the conduction band on TiO2. Hence, the open circuit potential, V-oc, for the devices prepared from D-sq, D-1-D-sq and D-sq-D(sq)were systematically modulated by controlling the intermolecular pi-pi and intramolecular dipole-dipole interactions of the dimeric dyes.